2023
DOI: 10.35408/comuybd.1197149
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Effect of Personal Values and Personal Traits as Mediator Variables on Job Satisfaction and Sales Performance

Abstract: Values and personality influence decision-making, motivation, attitude, interpersonal relationships, behavior, and performance. Personal values influence traits; people try to behave in a way that is consistent with their values. Values are the drivers of behavior, including workplace behavior. The relationship between personal values and behavioral outcomes may have been explored empirical studies in various disciplines but limited to a few studies in management. In addition, the effect of job values on perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 60 publications
0
0
0
Order By: Relevance
“…They lack confidence and their emotions are not stable [11]. Research by İlhan et al [20] found that job performance presented by neurotic individuals is in reverse order with other personalities. In the recruitment process, neuroticism is the most important personality trait that should be avoided when selecting a candidate.…”
Section: Neuroticismmentioning
confidence: 99%
“…They lack confidence and their emotions are not stable [11]. Research by İlhan et al [20] found that job performance presented by neurotic individuals is in reverse order with other personalities. In the recruitment process, neuroticism is the most important personality trait that should be avoided when selecting a candidate.…”
Section: Neuroticismmentioning
confidence: 99%